Morphological and quality attributes of garlic (Allium sativum L.) as affected by different planting methods - Akhtar, Naveed; Aftab, Muhammad; Sarwar, Ghulam; Hussain, Sarfraz; Idrees, Muhammad; Babar, Babar Hussain; Arif, Muhammad; Ramzan, Hafiz Naveed (Journal of Pure and Applied Agriculture, 2023)
A two-year field study was carried to evaluate effect of planting methods on morpho-quality traits of garlic with randomized complete block design having four repeats and plot size of 3.0 m × 5.0 m. Recommended dosage of fertilizer i.e., 140-85-125 kg ha-1NPK was used. Four treatments viz. P1 = Flat sowing (Conventional) (R × R = 20 cm), P2 = Ridge sowing (R × R = 30 cm) one row on each side of ridge, P3 = Ridge sowing (R × R = 75 cm) two rows on each side of ridge and P4 = Bed sowing (B × B = 150 cm) eight rows on the top of bed were studied. Results showed that all planting methods significantly affected the morpho-quality attributes of garlic than conventional planting. However, amongst planting P3 = Ridge sowing (R × R = 75 cm) two rows on each side of ridge considerably produced highest values of plant height (61.23 and 56.35 cm), No. of leaves per plant (7.50 and 8.50), average bulb girth (4.24 and 3.87 cm), average bulb weight (54.88 and 52.62 g), clove size (1.66 and 1.68 cm2), 100-clove weight (94.04 and 92.06 g), bulb yield (12520 and 12429 kg ha-1). Though, P3 = Ridge sowing (R × R = 75 cm) method produced total soluble solids (25.12 and 27.76 %), soluble proteins (10.40 and 11.52 mg g-1), soluble sugar (18.84 and 20.57 %), total sugar (10.70 and 12.28 mg g-1), total phenol (33.40 and 34.97 mg g-1) and total flavonoid (1.56 and 1.68 mg g-1) than rest of the planting methods. It was suggested that P3 = Ridge sowing (R × R = 75 cm) two rows on each side of ridge should be used for better growth and yield performance and quality in garlic production.